Theoretical approaches to understanding incest in psychological science - Hlushchenko, Mykyta (Psychological Prospects Journal, 2023)
Purpose. The paper aims to present the theoretical analysis of the incest concept in the scientific psychological discourse, to define the main aspects of the incest concept interpretation by different approaches, and to define the peculiarities of the incest manifestations in the familial system.Methods. The authors applied the techniques for the theoretical study of references on the topic (analysis, synthesis, generalization, comparison, systematization of different approaches) to analyze the incest phenomenon. The used methods present the comparative analysis of the incest concept, the specter of its manifestations in the family system, and the differentiation of the concepts such as “sexual exploitation of a child”, “physical incest", “emotional incest” and “pedophilia”.Results. As a result of the theoretical study, the wide specter of the incest concepts’ interpretations in psychological research and historical roots of defining the sexual relationship between adults and a child, to whom an adult is related, as an incest were outlined. The paper emphasizes that incest occurs in the family due to the extreme level of undifferentiated family roles, violation of the hierarchy, so that incest can be the means to reduce the anxiety level in the family and can take place in different generations. The authors systematized the forms and the types of the incest manifestations, focusing on the degree of the kinship between the subject and object involved, the type of the incestuous relationship and the type of sexual contact, mechanisms of committing the incest. They define that the concept of “emotional incest’ refers to the problem of the co-dependence between the family members and is not synonymous with the classic definition, which includes the physical sexual contact between the child and their blood-relative. It’s summarized that incest is a kind of sexual abuse of a child, which can result in psychological trauma.Conclusions. We can summarize that incest is a complex, poly-component problem and is studied in different psychological approaches. The incest phenomenon is represented by any sexually related behavior between the family members and the child. It was mentioned that the psychoanalytical approach interprets the problem of incestuous behavior from the point of Oedipal complex and the violations in personality normalized psychosexual development, while the representatives of the family-systems approach define the incest as a result of the breach in a hierarchical structure and family functioning. It is stated that regardless of the form of incest it is sexual abuse of a child and results in traumatic consequences.
Keywords: family; incest; physical incest; emotional incest; sexual abuse